The variety and limits of dairy policies in a context of global market deregulation - Daniel-Mercier Gouin; Aurélie Trouvé (Revue de la Régulation)
Since the 1980s, agricultural markets have been gradually deregulated. The milk sectors of the main dairy-exporting countries have not been shielded from these changes, which has led to a deeper global integration of dairy markets. However, a historical comparison of policies in the United States, New Zealand, the European Union, and Canada, from both a rural economy and regulationist perspective, reveals that a variety of institutional frameworks exist. For instance, Canada’s dairy sector continues to be highly regulated by public authorities, unlike in the case of New Zealand. Both countries, though, along with the United States, guarantee farmers a minimum share of the added value from processing, contrary to what is practiced in France. Market deregulation in the European Union has also brought about different national forms of competition. Based on the dairy sector, this analysis supports the idea of a great diversity of national forms of state and regulation, adapting to the global capitalist and neo-liberal regime. However, the latter generates major contradictions, disputing the sustainability of each of these forms of national regulation.